A level set-based procedure for the cohesive modeling of yarn–yarn contacts in woven composite RVEs. (15th January 2023) - Li, Anqi; Ehab Moustafa Kamel, Karim; Wintiba, Badadjida; Remmers, Joris J.C.; Geers, Marc G.D.; Massart, Thierry J.
Abstract: Decohesion processes involved in debonding between yarns and matrix or sliding between contacting yarns constitute important failure mechanisms in woven composites. The geometry of the yarn architecture however makes it difficult to avoid interpenetrations between neighboring yarns in their geometrical description. This motivated recent works using a level set-based methodology to generate smooth geometries without interpenetration for generated Representative Volume Elements (RVEs) and experimental image-based samples. Such tools require introducing gaps between contacting yarns, which may be debatable when taken too large or may be computationally costly for thin gap, locally dictating the mesh size. To avoid this, the yarns contacting surfaces can be discretized using interface elements. Yet, identifying such contacting surfaces is complex. An implicit geometry description based on distance fields is used here to extract a geometry that supports cohesive zones, identifying the interface of yarn–yarn contacts and eliminating the gaps using manipulations on distance fields of the individual yarns. This allows generating conforming tetrahedral meshes with inserted cohesive elements in the contact areas. The methodology is shown to reduce the size of finite element models of woven composite RVEs by over two orders of magnitude, thereby paving the way towards affordable damage simulations on such RVEs.